Tom Stoppard: European Phantom Pain and the Theatre of Faux Biography - Eckart Voigts (Humanities, 2021)
The paper reads Stoppard’s work in the 21st century as further testimony of the gradual politicisation of his work that began in the 1970s under the influence of Czech dissidents, and particularly as a result of his visits to Russia and Prague in 1977. It also provides evidence that Stoppard, since the 1990s, had begun to target emotional responses from his audience to redress the intellectual cool that seems to have shaped his earlier, “absurdist” phase. This turn towards emotionalism, the increasingly elegiac obsession with doubles, unrequited lives, and memory are linked to a set of biographical turning points: the death of his mother and the investigation into his Czech-Jewish family roots, which laid bare the foundations of the Stoppardian art. Examining this kind of “phantom pain” in two of his 21st-century plays, Rock’n’Roll (2006) and Leopoldstadt (2019), the essay argues that Stoppard’s work in the 21st century was increasingly coloured by his biography and Jewishness—bringing to the fore an important engagement with European history that helped Stoppard become aware of some blind spots in his attitudes towards Englishness.